Marked increase in cerebrospinal fluid glial fibrillar acidic protein in neuromyelitis optica: an astrocytic damage marker. Issue 5 (16th April 2009) - Misu, T; Takano, R; Fujihara, K; Takahashi, T; Sato, S; Itoyama, Y
Abstract : Background: Neuromyelitis optica (NMO) is a neurological inflammatory disease associated with autoimmunity to aquaporin 4, predominantly localised in astrocytic foot processes. Recent studies have revealed that loss of aquaporin 4 and glial fibrillar acidic protein (GFAP) is a prominent feature of NMO lesions, suggesting astrocytic impairment. Objective: To reveal a useful clinical biomarker of NMO. Methods: Enzyme-linked immunosorbent assays were carried out for astrocytic markers GFAP and S100B in CSFs, obtained from the patients with NMO (n = 10) and multiple sclerosis (MS) (n = 10) manifesting acute myelitis, acute disseminated encephalomyelitis (ADEM) (n = 3), spinal infarction (n = 3), and other neurological diseases (OND) (n = 5). Results: The CSF-GFAP levels during relapse in NMO (7666.0 (SD 15 266.5) ng/ml) were significantly over several thousand times higher than those in MS (0.7 (1.5)) or OND (0.6 (0.3)), and considerably higher than those in spinal infarction (354.7 (459.0)) and ADEM (0.4 (0.2)). They returned close to normal levels along with clinical improvement soon after corticosteroid therapy in NMO. There were strong correlations between the CSF-GFAP or S100B levels and expanded disability status scales or spinal lesion length in NMO (r>0.9). Conclusions: CSF-GFAP and S100B may be clinically useful biomarkers in NMO, and astrocytic damage is strongly suggested in the acute phase of NMO.